Eigenvalues of the Laplacian under the Ricci flow - Luca Fabrizio Di Cerbo (Rendiconti di Matematica e delle Sue Applicazioni, 2007)
We derive, under a technical assumption, the first variation formula for the eigenvalues of the Laplacian on a closed manifold evolving by the Ricci flow and give some applications.